Estimation of stability derivative of an oscillating cone in hypersonic flow - Shabana, Ayesha; Monis, Renita Sharon; Crasta, Asha; Khan, Sher Afghan (Institute of Institutional Industrial Research, 2017)
Formulae for the Stiffness and Damping derivatives are obtained in a closed form in the present context with the assumptions that the gas is non-viscous and perfect, the motion is quasi-steady and quasi-axisymmetric, and the nose semi angle of the cone is such that the Mach number M2 behind the shock 2 M < 2.5 . Results are presented for cone for gamma = 1.4 ,at different Mach numbers and semi angles of the cone. It is observed that the neutral point shifts away from the apex of the cone as semi angle increases. So is the case with the minimal of the curves for damping derivative. Also it is seen that an increase in Mach number after 10 marginally contributes to any variations in the values of stiffness and Damping derivative which is in accordance with the Mach number independence Principle. These results are likely to find wide applications in high speed flow problems.